Features of flowering cousinia felted (Cousinia tomentella Winkl) - Islamov Buston Sultanovich (International Journal of Advanced Science and Technology, 2020)
The paper analyses the features of flowering cousinia felted (Cousinia tomentella Winkl). In this case, the author studies plant antecology from not only practical perspective, but also theoretically. Thus, following questions of flowering have been successfully studied and developed in the article: the beginning of flowering of cousinia felted, pollination, the daily flowering rhythm, morphology and pollen vitality. To conclude with, outcomes and shortcomings while offering better development possibilities for the future research.